1998
DOI: 10.4319/lo.1998.43.2.0273
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of trace elements in a marine copepod

Abstract: We measured assimilation efficiencies (AEs) from ingested algal food, uptake rates from the dissolved phase, and efflux rate constants of five trace elements (Ag, Cd, Co, Se and Zn) in the marine copepod Temora longicornis.AEs of Ag, Cd, Co, Se, and Zn from two diatom diets were 13, 35, 14, 59, and 61%, respectively. AEs of metals from ingested natural seston collected during the spring phytoplankton bloom in Long Island Sound were comparable to AEs from diatoms. The assimilation of all trace elements within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
179
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 198 publications
(202 citation statements)
references
References 32 publications
(55 reference statements)
20
179
3
Order By: Relevance
“…These values are within the ranges determined for other bivalves (Mytilus edubs, Mercenaria rnercenaria, and Crassostrea viryinlca) , Reinfelder et al 1997. However, the rate constants of loss froin the bivalves in this and other studies are considerably lower than the values (0.07 to 0.3 d-') reported for crustacean zooplankton (Wang & Fisher 1998).…”
Section: Efflux Ratescontrasting
confidence: 50%
“…These values are within the ranges determined for other bivalves (Mytilus edubs, Mercenaria rnercenaria, and Crassostrea viryinlca) , Reinfelder et al 1997. However, the rate constants of loss froin the bivalves in this and other studies are considerably lower than the values (0.07 to 0.3 d-') reported for crustacean zooplankton (Wang & Fisher 1998).…”
Section: Efflux Ratescontrasting
confidence: 50%
“…This may explain the positive enrichment (BMF Ͼ 1.0) of Hg, Zn, and Cd we find in zooplankton. Wang and Fisher (1998) also found that the assimilation efficiency of Zn by marine copepods from phytoplankton was the highest relative to Cd, Co, and Se, and Ͼ50% of Zn was from ingested food. Efficient assimilation of Zn by zooplankton may help explain Zn biomagnification in zooplankton and fish in this study.…”
Section: Predictors Of Metal Concentrations In Zooplankton-mentioning
confidence: 91%
“…Given the relatively similar biomass dry weight among the three size fractions (Table 1), the much higher surface area : volume ratios in the smaller plankton may also explain the observation of the smaller the plankton, the higher the metal quotas. Since the smaller phytoplankton would be grazed by zooplankton, part of the metals on the phytoplankton would be digested and absorbed and part of them would be repacked into fecal pellets before being transported into deep waters as sinking particles (Wang and Fisher 1998). Determining how the abiogenic particles on the phytoplankton are recycled in the deep waters, after being grazed and repackaged to fecal pellets through grazer's gastrointestinal environment, is important for illustrating the whole picture of the internal cycling of the trace metals in oceanic water columns.…”
Section: Discussionmentioning
confidence: 99%